IMPLEMENTASI UNDANG-UNDANG NOMOR 14 TAHUN 2005 DALAM PENINGKATAN KUALIFIKASI AKADEMIK GURU SD MELALUI PENDIDIKAN TINGGI JARAK JAUH DI WILAYAH KABUPATEN BELITUNG - Sofjan Aripin; Latifah Alton (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2010)
The policy is a fundamental reference for the implementer, but policy implementation is the determinant of the policy is successful or fails. Act (Act) No. 14 of 2005, is one reference in the implementation of policy and academic qualification programs for teachers and lecturers to improve competence in the field. Government through the Ministry of National Education, and local government as a policy implementer on the ground that the 2015 target should be a qualified teacher Strata 1 (S1). Government District Education Office Belitung ups have targeted that by 2013 all primary school teachers (SD) have already qualified S1. Some constraints in the implementation of the program can not be avoided but these obstacles can be overcome through the distance education carried out in cooperation with the Unit of Distance Learning Courses Open University (UPBJJ-UT) Pangkalpinang.